2021
DOI: 10.1021/acs.analchem.1c04108
|View full text |Cite
|
Sign up to set email alerts
|

7-Aminocoumarin-4-acetic Acid as a Fluorescent Probe for Detecting Bacterial Dipeptidyl Peptidase Activities in Water-in-Oil Droplets and in Bulk

Abstract: Droplet-based microfluidic systems are a powerful tool for biological assays with high throughput. Water-in-oil droplets (WODLs) are typically used in droplet-based microfluidic systems to culture microorganisms and perform enzyme assays. However, because of the oil surrounding the nanoliter and picoliter volumes of WODLs, availability of suitable substrates is limited. For instance, although 7-amino-4-methylcoumarin (AMC) is commonly used as a fluorescent probe of the substrate to detect peptidase activity, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…UV–vis absorption and fluorescence spectroscopies are the two most used methods in chemistry, biology, and materials sciences. Understanding the relationship between the fluorophore light absorption and fluorescence emission is important not only for a fundamental understanding of materials photophysical properties but also for reliable fluorescence analysis. While the origins of light absorption and fluorescence emission have become common knowledge for most fluorescent materials, the interplay among the sample light absorption and emission can be highly complicated in many practical fluorescence applications. Mechanistically, fluorophore light absorption must precede its fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…UV–vis absorption and fluorescence spectroscopies are the two most used methods in chemistry, biology, and materials sciences. Understanding the relationship between the fluorophore light absorption and fluorescence emission is important not only for a fundamental understanding of materials photophysical properties but also for reliable fluorescence analysis. While the origins of light absorption and fluorescence emission have become common knowledge for most fluorescent materials, the interplay among the sample light absorption and emission can be highly complicated in many practical fluorescence applications. Mechanistically, fluorophore light absorption must precede its fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet microfluidics has been widely applied in the discovery and directed evolution of enzymes because of its low cost and high throughput. 44 Microbial cells and enzymes with the desired activities have been isolated based on the characteristics of the microdroplets, such as fluorescence, 9,11 absorbance, 14,15 Raman scattering, 16 electrochemical detection, 17,18 and mass spectrometry. 19,20 In this study, we demonstrated that enzymatic hydrolysis of agarose can be assayed in microdroplets based on their deformability (Figures 3 and 4).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Using a fluorogenic substrate, we identified novel β-glucosidase genes from uncultured bacterial cells in marine samples . In addition to fluorescence, , multiple readouts, including absorbance, , Raman scattering, electrochemistry, , and mass spectrometry, , are compatible with enzymatic assays in microdroplets. However, it is challenging to assay the enzymatic degradation of macromolecules in microdroplets by using conventional assays.…”
mentioning
confidence: 99%
“…Micro-space-based cultivation methods have recently been attracting attention with a view to improving screening efficiency. [12][13][14][15] Micro-droplet methods have been developed as a contribution to cultivation technology based on microspace. 16,17 Droplets of a few mm to a hundred mm in diameter are produced by droplet generators, 18 and then the microorganisms enclosed inside the droplets are evaluated with a cell sorter.…”
Section: Introductionmentioning
confidence: 99%